Imposition of Income Tax in Swap of Immovable Property (Swap Asset) - Djaja, Benny; Illona, Illona (Faculty of Law, Universitas Pekalongan, 2024)
Exchange agreements for immovable objects are still carried out in the community, especially in exchange agreements for land and building objects. This article discusses the lack of detailed regulation on the imposition of income tax for the exchange of immovable objects, such as land and buildings, in Indonesia. It explains the importance of taxes as a source of revenue for the government and explores the differences between central and local taxes, as well as how taxes are closely related to legal relations in civil law. This research uses normative legal research methods. The results show that the legal relationship outlined in an agreement called exchange is equated with buying and selling which is subject to income tax. The exchange that is carried out and equated to buying and selling from the understanding of the object of income tax is not appropriate. This incompatibility is because the exchange is essentially carried out not to obtain profit. This article concludes by highlighting the need for more detailed regulations on the imposition of income tax for the exchange of immovable objects, as it cannot be equated with a sale and purchase transaction.